The Cambridge History of Latin American Law in Global Perspective - Duve, Thomas (Cambridge University Press, 2025)
This volume provides an overview of Latin American law from the pre-colonial period to the present, showcasing commonalities and differences. Written by international experts, it will be the standard reference for legal scholars and historians. This title is also available as Open Access on Cambridge Core.